Genetic analysis of the zinc finger in the Moloney murine leukemia virus nucleocapsid domain: replacement of zinc-coordinating residues with other zinc-coordinating residues yields noninfectious particles containing genomic RNA. - Gorelick, R J (1996)
The effect of changing zinc (Zn2+)-coordinating residues in the nucleocapsid protein of Moloney murine leukemia virus was investigated by introducing a His-34-to-Cys or Cys-39-to-His mutation into the putative Zn2+ finger. Mutant virions contained normal levels of properly processed Gag and Env proteins and wild-type levels of full-length viral RNA. However, the specific infectivity of the mutants was approximately 4 x 10(-4) that of wild-type particles. They were probably noninfectious because of the inability of the particles to synthesize cDNA transcripts, since full-length viral DNA could not be detected in Hirt supernatants of NIH 3T3 cells infected with the CCCC or CCHH virus. These mutants will provide an extremely valuable tool for analysis of the role of retroviral Zn2+ fingers in infection processes, independent of viral RNA recognition and packaging.